Age and ovarian development are related to worker personality and task allocation in the ant Leptothorax acervorum. Issue 3 (1st June 2014) - Kühbandner, Stephan; Modlmeier, Andreas P.; Foitzik, Susanne
Abstract: In social insects, workers of different morphological castes and age are known to act differently. Yet, it is unclear how body size and ovarian development influence worker personalities (i.e. consistent behavioral variation) and task allocation in similar aged ant workers of monomorphic species. Behavioral variation is thought to be a key element of division of labor, but few studies have linked worker personality to task allocation. We investigated individual behavior in Leptothorax acervorum ant workers at two time points during the first three months of their life and in two different settings. We observed worker behavior in the nest (i.e. task allocation) and in standardized aggression, exploration and brood care experiments (i.e. personality) and found behavioral repeatability in foraging and exploration. Further, workers acted consistently across settings: workers with a more aggressive and exploratory personality type were more active in the nest. Moreover, ovarian development was associated with worker personality and task allocation: older workers with well-developed ovaries foraged less, but were more aggressive and exploratory. In accordance with the typical age-polyethism of social insects, workers became more active and foraged more as they grew older. Consequently, our study suggests that task allocation in Leptothorax acervorum is not only influenced by ovarian development and age, but moreover by the personalities of its workers.